Probability of remission of juvenile idiopathic arthritis following treatment with steroid joint injection - Sato, Juliana De Oliveira [UNESP]; Fernandes, Taciana De Albuquerque Pedrosa [UNESP]; Do Nascimento, Carolina Bicalho [UNESP]; Corrente, Jose Eduardo [UNESP]; Saad-Magalhães, Claudia [UNESP] (My University, 2014)
Objective: Steroid joint injection is indicated as starting treatment for juvenile idiopathic arthritis, but its effect as single treatment has not been explored. Our aim was to estimate arthritis remission probability after single or repeated injections. Methods: Conduct a retrospective analysis of inactive arthritis status, remission on medication and remission off medication, estimating cumulative probability and mean time to survival, from the first joint injection session to the last follow-up visit or disease-modifying anti-rheumatic drugs initiation. Remission and time to achieve remission status after single or repeated injections were compared. Results: Seventy-seven patients with 4-year medium follow-up and 254 treated joints, were reviewed. Eighty-three percent of the individuals had oligoarticular subtype and 57% had persistent oligoarticular course. Overall, 26% achieved remission off medication status, 4% remission on medication and 38% initiated disease-modifying anti-rheumatic drugs. Survival analysis resulted in mean time of achieving inactive disease status, remission on medication and off medication of 8, 11 and 56 months, respectively. The cumulative probability of remission off medication was 2% at 12 months, 8% at 24 months and 18% at 36 months. Frequency of inactive disease, remission on medication and remission off medication status decreased proportionally following repeated joint injections in comparison with the frequency of the same status for those receiving single treatment. Conclusion: The dropout rates due to anti-rheumatic drugs initiation indicated limited long-term benefits of intra-articular steroids for juvenile idiopathic arthritis. © Clinical and Experimental Rheumatology 2014.
Keywords: Juvenile idiopathic arthritis; Remission; Triamcinolone hexacetonide